Gerakan Sosial Akar Tuli Dalam Mengadvokasi Hak Tuli di Kota Malang - Wama Yahya; Ucca Arawindha (Sociology Department, Brawijaya University, 2022)
ABSTRACT The Malang City in Indonesia, declares itself to be inclusive city, but it turns out that there are still many people with disabilities’ – deafness – rights seem not been fulfilled, one of which become the focus of this research. For deaf people, one of their efforts to seek the fulfillment of their rights is to form a collectivity. For that reason, the Akar Tuli was built, with the motive to bring Deaf youth into a forum which allows them to voice their rights. This study aims to determine, analyze and describe how social action of Akar Tuli as a social movement through advocation for the rights of deaf people in Malang City. This research uses the New Social Movement Theory, namely ‘The Identity-Oriented Theory’ that seek the explanation of how this community carries out social movements to achieve their goals by their identity. As a community, there would be a very strong reason for Akar Tuli to keeps them going to carry out various kinds of movements. That is, the fulfillment of the rights of deaf people to the sign language they use to communicate and also as their identity. Sign language is the strengthen for Akar Tuli to socialization and education about the disability rights by collaborate with government or non-government organization in Malang. Furthermore, accessibility is also a keypoint for them. The conclusion is Akar Tuli take social action as social movement that aims to encourage disability awareness in Malang City. Hopefully, the Deaf people have the same rights as a citizen, even though their communicate in different ways.